2012
DOI: 10.1590/s0101-20612012005000026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat treatment and storage temperature on the use of açaí drink by nutraceutical and beverage industries

Abstract: This study assesses the storage temperature effect on the anthocyanins of pasteurized and unpasteurized açaí pulp. The data was obtained using a pasteurized and lyophilized pulp (PLP) to evaluate the temperature effect (0, 25, and 40 °C). Part of non-pasteurized frozen pulp (NPP) was pasteurized (NPP-P) at 90 °C for 30 seconds; both pulps were stored at 40 °C. The anthocyanin content reduction in the drink was evaluated from the half-life time (t1/2), activation energy (Ea), temperature quotient (Q10),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
2
11
0
3
Order By: Relevance
“…It is clear from Figure 2 and Table 2 that the degradation of blackberry anthocyanins from ethanolic extract followed second order reaction kinetics with respect to the illuminance of the light source (greater values for R 2 ). This model has also been reported by Albarici & Pessoa [14] for degradation anthocyanins from nonpasteurized acai pulp due to temperature effects. In that study, the concentration of anthocyanins decreased exponentially over time, showing halflife (t 1/2 ) = 10.14 hours.…”
Section: Kinetic Modeling For the Extract Without Storagesupporting
confidence: 83%
“…It is clear from Figure 2 and Table 2 that the degradation of blackberry anthocyanins from ethanolic extract followed second order reaction kinetics with respect to the illuminance of the light source (greater values for R 2 ). This model has also been reported by Albarici & Pessoa [14] for degradation anthocyanins from nonpasteurized acai pulp due to temperature effects. In that study, the concentration of anthocyanins decreased exponentially over time, showing halflife (t 1/2 ) = 10.14 hours.…”
Section: Kinetic Modeling For the Extract Without Storagesupporting
confidence: 83%
“…In unpasteurized +peach juice the TAC declined according to pseudo 2nd‐order kinetics. Interestingly, the degradation of anthocyanins in unpasteurized acai pulp followed 2nd‐order kinetics whereas pasteurized pulp decreased according to 1st‐order kinetics (Albarici and Pessoa ).…”
Section: Resultsmentioning
confidence: 98%
“…Although most of the available studies indicate that thermal treatment reduces the levels of bioactive compounds, there is still controversy about it (Rawson et al, 2011). Albarici & Pessoa (2012) showed that pasteurization at 90 °C for 30 seconds reduced the degradation rate of anthocyanins compared to that of the unpasteurized pulp. Dn the other hand, these authors also demonstrated the importance of using low temperatures during processing and storage to increase the stability of anthocyanins.…”
Section: Step 2 -Changes During Storage Of the Low-fat Açaí And Cupuamentioning
confidence: 99%
“…In recent years, there has been a significant increase in demand for this product in the domestic and international markets due to the nutritional properties of açaí berry, which has high levels of lipids, proteins, fiber, vitamin E, and minerals (Alexandre et al, 2004). Açaí is also rich in anthocyanins, pigments with antioxidant properties that have been associated with various health benefits (Albarici & Pessoa, 2012;Pacheco-Palencia et al, 2009;Del-Pozo-Insfran et al, 2006;Rogez, 2000).…”
Section: Introductionmentioning
confidence: 99%